MiR-451a Inhibited Cell Proliferation and Enhanced Tamoxifen Sensitive in Breast Cancer via Macrophage Migration Inhibitory Factor. (16th June 2015) - Liu, Zhenru; Miao, Tianyu; Feng, Ting; Jiang, Zhouhua; Li, Mingyuan; Zhou, Liming; Li, Hong
Abstract : This study aims to investigate the regulative effects of microRNA-451a (miR-451a) on cell proliferation and sensitivity to tamoxifen in breast cancer cells. In cell culture experiments, the lentiviral vectors of pHBLV-miR-451a and pHBLV-miR-451a sponge were constructed and used to transfect MCF-7 and LCC2 cells. The transfection efficiency was tested by fluorescent observation, and cell lines with stable over- or downregulated expression of miR-451a were established. The expression of miR-451a and the target gene macrophage migration inhibitory factor (MIF) were detected by real-time reverse transcriptase polymerase chain reaction and/or western blot. Moreover, MTT assay, colony formation, and Transwell invasion assays were also performed. Data showed that the recombinant lentiviral vectors were constructed correctly, and the virus titer was 1 × 10 8 CFU/mL. The stable transfected cells were obtained. Overexpression of miR-451a downregulated MIF expression in mRNA and protein levels and inhibited cell proliferation, colony formation, and invasion of breast cancer cells. Downregulation of miR-451a upregulated MIF expression and increased breast cancer cell growth, invasion, and tamoxifen sensitivity. In summary, the miR-451a/MIF pathway may play important roles in the biological properties of breast cancer cells and may be a potential therapeutic target for breast cancer.